TINGKAT BAHAYA EROSI DAN FAKTOR KEAMANAN LERENG PADA JALAN BANDA ACEH - CALANG - Ervina Roeska; Yuhanis Yunus; Sofyan M. Saleh (JURNAL TEKNIK SIPIL, 2017)
Abstract: Soil erosion is the removal of soil from one place to another by water or wind. The depletion of soil layers at the top of slope causes decreased the ability of the soil on slopes, and the ability of soil to absorb water (Asdak, 1995). Erosion Danger Level (TBE) is an assessment or prediction on the magnitudes of soil erosion and potential danger on the road. The TBE is determined based on comparisons between the magnitudes of annual soil loss (A) and Soil Erosion Tolerance (TSL) (Arsyad, 2000). The TSL for the region of Sumatra is 27 – 29 ton/ha/year (Surbakti, 2009). The slopes of the 240 KM road built by USAID in 2006, linking Banda Aceh to Calang, are erosion prone areas and the current condition is considerably not safe. This research aims at calculating the erosion rate that was still tolerance, the magnitude of TBE and the slopes safety factor (Fs). The research locations were in 3 observation areas, that is, at KM.35, KM.104, and KM.129. The Universal Soil Loss Equation (USLE) methods were used to calculate the erosion rate. The USLE parameters in this research were rainfall erosivity (R) for 10 years, soil erodibility (K) with samplings by using disturbed sample (T1) and undisturbed sample (T2) by means of hand bore, measurement slope length and slope strength (LS)  which was calculated by using Theodolite Station, visual observations for cover and land management (CP). The analysis results showed that the Erosion Danger Level (TBE) at KM.35 (T1) was 11.82; KM.35 (T2) 19.38; KM.104 (T1) 15.45; KM.104 (T2) 20.02; KM.129 (T1) 17.81; and KM.129 (T2) 19.46 respectively. The measurement results on TBE showed that the overall point of the test site was in very heavy criteria. The calculation results of slopes safety factor (Fs) at KM.35, KM.104, and KM.129 testing point (T2) were 0.287; 0.227; and 0.436 respectively. The calculation results of slopes safety factor (Fs) at all research locations were on the unsafe condition (Fs 1).Keywords : Erosion Danger Level (TBE), Slope Safety Factor (Fs), Road Slope Erosion.Abstrak: Erosi tanah adalah peristiwa terangkutnya tanah dari satu tempat ke tempat lain oleh air atau angin, menipisnya lapisan tanah pada lereng bagian atas yang menyebabkan menurunnya kemampuan tanah pada lereng, dan menurunkan kemampuan tanah untuk menyerap air (Asdak, 1995). Tingkat Bahaya Erosi (TBE) merupakan penilaian atau prediksi terhadap besarnya erosi tanah dan berpotensi bahaya terhadap badan jalan. TBE ditentukan berdasarkan perbandingan antara besarnya laju erosi tanah (A) dengan erosi tanah yang ditoleransikan (Arsyad, 2000) untuk wilayah Sumatera TSL yaitu 27 – 29 ton/ha/thn (Surbakti, 2009). Lereng di jalan Banda Aceh–Calang yang di bangun oleh USAID tahun 2006 sepanjang 240 KM di Kabupaten Aceh Besar dan Aceh Jaya yang sering mengalami erosi dan kondisi lereng tidak aman. Penelitian ini bertujuan untuk menghitung besarnya TBE dan faktor keamanan lereng (Fs). Lokasi penelitian ini berada di 3 titik pengamatan pada KM.35, KM.104, dan KM.129. Metode USLE (Universal Soil Loss Equation) digunakan untuk menghitung laju erosi. Parameter USLE dalam penelitian ini meliputi, erosivitas hujan (R) selama 10 tahun, erodibilitas tanah (K) dengan pengambilan sampel tanah secara terganggu/disturbed sample (T1) dan tidak terganggu/undisturbed sampel (T2) dengan bor tangan, mengukur panjang dan kemiringan lereng (LS) dengan Theodolite Station, pengamatan visual untuk penutup dan pengelolaan lahan (CP). Hasil analisis menunjukkan Tingkat Bahaya Erosi (TBE) di KM.35 (TI) = 11,82; KM.35 (T2) = 19,38; KM.104 (T1) = 15,45; KM.104 (T2) = 20,02; KM.129 (TI) = 17,81; dan KM.129 (T2) = 19,46. Hasil pengukuran terhadap TBE memperlihatkan bahwa keseluruhan titik lokasi pengujian berada dalam kriteria sangat berat (SB). Hasil perhitungan terhadap faktor keamanan lereng (Fs) pada titik pengujian adalah KM.35 (T2) = 0,287; KM.104 (T2) = 0,227; dan di KM.129 (T2) = 0,436. Hasil perhitungan faktor keamanan lereng (Fs) pada semua lokasi penelitian berada pada kondisi tidak aman (Fs 1).Kata kunci : Tingkat Bahaya Erosi (TBE), Faktor Keamanan Lereng (Fs), Erosi Lereng Jalan.